Dynamical systems with applications using mathematica - Lynch, Stephen (Boston, Birkhauser, 2007)
This book provides an introduction to the theory of dynamical systems with the aid of the Mathematica® computer algebra package. The book has a very hands-on approach and takes the reader from basic theory to recently published research material. Emphasized throughout are numerous applications to biology, chemical kinetics, economics, electronics, epidemiology, nonlinear optics, mechanics, population dynamics, and neural networks. Theorems and proofs are kept to a minimum. The first section deals with continuous systems using ordinary differential equations, while the second part is devoted to the study of discrete dynamical systems.
Bibliographical references 451-468p.; Index 469-484p.
Keywords: Calculus-mathematical analysis; Differentiable dynamical systems; Differential dynamical systems; Mathematical-Computer file; Mathematics